2023
DOI: 10.1021/acs.jpcc.3c00998
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Response of CdSe Quantum Dots to Hydrostatic Pressure

Abstract: The size-dependent pressure response of oleatestabilized CdSe quantum dots (QDs) in paraffin is investigated using diamond anvil cell experiments and density functional theory (DFT). For QDs above 3.0 nm, the photoluminescence shows a blue-shift of around 43 meV/GPa, close to the value for bulk CdSe, but the shift increases strongly for nanocrystals less than 3 nm in size. Conversely, the absorption shift is 45 meV/GPa above 3.0 nm but weakens to 35 meV/GPa for particles 1.5 nm in size. No crystallographic pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 94 publications
0
18
0
Order By: Relevance
“…In this context, it is important to distinguish their fluorescence from the fluorescence of QDs, which are semiconducting nanoparticles constituting an indefinite number of atoms. While the fluorescence in atomic NCs originates from HOMO–LUMO transitions, akin to molecules, quantum confinement is the major origin of emission in QDs, whereas the size of the QD determines the energy difference between the conductance and valence bands, i.e., the emission of the QD. As stated, atomic NCs, as opposed to other forms of nanoscale particles, have consistent structural integrity and their chemical composition can be expressed in terms of precise chemical formulas. Thus, any polydispersity that prevails in other common forms of nanoscale particles is hardly present for atomic NCs, and the structure–property relationship of atomic NCs can be defined reliably .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is important to distinguish their fluorescence from the fluorescence of QDs, which are semiconducting nanoparticles constituting an indefinite number of atoms. While the fluorescence in atomic NCs originates from HOMO–LUMO transitions, akin to molecules, quantum confinement is the major origin of emission in QDs, whereas the size of the QD determines the energy difference between the conductance and valence bands, i.e., the emission of the QD. As stated, atomic NCs, as opposed to other forms of nanoscale particles, have consistent structural integrity and their chemical composition can be expressed in terms of precise chemical formulas. Thus, any polydispersity that prevails in other common forms of nanoscale particles is hardly present for atomic NCs, and the structure–property relationship of atomic NCs can be defined reliably .…”
Section: Introductionmentioning
confidence: 99%
“…However, for d E g /d T , a reduction of 20% from the bulk value d E bulk /d T requires a particle size as small as 1.0 nm, which is significantly smaller than the Bohr radius. We refer to this as the EC regime, as shown for d E g /d P …”
mentioning
confidence: 99%
“…However, recent studies have shown that some properties of QDs, such as the bandgap pressure coefficient (dE g /dP), 9 do not exhibit size dependence in the normal confinement regime but do so only in the "extreme confinement" (EC) regime. 9 The temperature dependence of the bandgap [E g (T)] is another fundamental property of semiconductors, and it provides insights into the underlying physical processes that affect the performance and reliability of semiconductor materials under different operating conditions. The strength of this temperature dependence can usually be described by its first temperature derivative, dE g /dT.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to the noninjection-based approach, , a reaction can be readily stopped in the prenucleation stage, which is almost impossible for the injection-based approach. , Prenucleation clusters that are relatively transparent in optical absorption were trapped. They form via chemical self-assembly, that occurs prior to nucleation and growth of QDs. These prenucleation clusters can transform to magic-size clusters (MSCs) and QDs. Thus, a multistep nonclassical model should be taken into account to understand the nucleation and growth of colloidal QDs, instead of the one-step classical LaMer model . It is highly possible that MSCs and QDs are regulated differently in relation to quantum size effects because shape comes into play for the former. ,, On a side note, CdSe MSCs (with a size of ∼1.2 nm and optical absorption peaking at ∼415 nm) were produced in the hot-injection approach; the bandwidth of MSCs is narrower due to the almost complete absence of size distribution.…”
mentioning
confidence: 99%